Thorax radiotherapy using 18F-positron emission tomography/computed tomography-guided precision radiotherapy is a prognostic factor for survival in patients with extracranial oligometastatic non-small cell lung cancer:A two-center propensity score-matched analysis - Liu, Cheng-Sen; Song, Ying-Qiu; Wang, Run-Ze; Wang, Zheng; He, Rong; Xu, Ke; Wang, Chen-Yu; Wu, Yu; Wang, Ye; Zhang, Xiao-fang; Li, Guang; Wang, Tian-Lu (Frontiers in Oncology, 2022)
Background: This retrospective study compared positron emission tomography (PET)/computed tomography (CT) and CT in the treatment of extracranial oligometastatic non-small-cell lung cancer (NSCLC) and explored the impact of thorax radiotherapy (TRT) on patient survival. Methods: We reviewed the medical records of Chinese patients with stage IV extracranial oligometastatic NSCLC who underwent PET/CT or CT at two centers. Propensity score matching (PSM) was used to control differences in patient characteristics between the maintenance chemotherapy alone and TRT plus maintenance chemotherapy groups. Results: We analyzed 192 eligible patients. The median survival time was better in patients who received PET/CT than in those who only received CT (n = 192, 16 months vs. 6 months, p＜0.001). Subgroup analysis showed the median survival time was significantly longer in the TRT plus maintenance group than in the chemotherapy alone group in patients who underwent PET/CT examinations (n = 94, 25 months vs. 11 months, p<0.001). However, there was no statistical difference in survival between both groups in patients who underwent CT examinations (n = 98, 8 months vs. 5 months, p = 0.180). A multifactorial analysis revealed a more favorable prognosis in patients who underwent PET/CT evaluation (HR: 0.343, 95% CI: 0.250-0.471, p <0.001) and TRT (HR: 0.624, 95% CI: 0.464-0.840, p = 0.002,) than in those who did not. PSM was consistent with these results. Conclusions: PET/CT-guided TRT is associated with improved clinical outcomes in patients with stage IV extracranial oligometastatic NSCLC.